We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
179
2
avatar+87 

Generalize the pattern by finding the nth term.

 

6, 10, 14, 18, 22

 Jun 4, 2019
 #1
avatar+6046 
+2

\(\text{Assuming $6$ is term #1}\\ s_n = 2+4n\)

.
 Jun 4, 2019
 #2
avatar+8829 
+3
the__ 1st__ term__ =__ 6        
the 2nd term = 6 + 4        
the 3rd term = 6 + 4 + 4 = 6 + 4(2)__ =__ 6 + 4(3 - 1)
the 4th term = 6 + 4 + 4 + 4__ =__ 6 + 4(3) = 6 + 4(4 - 1)
                 
the nth term = 6 + 4(n - 1)        
 Jun 4, 2019

13 Online Users

avatar